CAN THE ETHNOSCIENCE-BASED INQUIRY LEARNING MODEL IMPROVE STUDENTS’ SCIENCE PROCESS SKILLS? - Saija, Maryone; Tahya, Dominggus (Molluca Journal of Chemistry Education (MJoCE), 2023)
This study aims to determine the increase in students' science process skills by applying an ethnoscience-based inquiry learning model to colloid system material from a public high school in West Seram. The type of research used is descriptive-quantitative. The sample used in this research was 30 students in class XI IPA. Data collection techniques in this study were test techniques in the form of a pre-test and a post-test. The results showed that the application of the ethnoscience-based inquiry learning model succeeded in improving students' science process skills, with an increased score calculated based on the results: the average value before learning was 26.29 and increased after learning with an average value of 80.50. The average value of N-gain is 0.74, indicating an increase in students' science process skills in the high category. Encouraging chemistry teachers to explore other ethnosciences to teach colloid systems is necessary.